Analisis Hambatan Komunikasi Lintas Budaya pada Mahasiswa Suku Mbojo dan Suku Samawa di Universitas Teknologi Sumbawa - Oktapiansyah, Yuda; Taubih, Lalu Ahmad (YASIN, 2024)
This research was conducted at the Sumbawa University of Technology to determine the barriers to cross-cultural communication among Mbojo and Samawa Tribe Students. The method used in this research was Qualitative Descriptive and used Porpusive Sampling to determine sampling. The research subjects were Samawa Tribe Students and Mbojo Tribe Students. In this research the researcher used Uncertainty Reduction Theory to obtain the desired results in the research to be conducted. So, the results of this research are that in language differences there are barriers to cross-cultural communication, then in differences in norms/customs there are various kinds of obstacles that occur due to cultural norms or habits, and finally in the lack of self-confidence both subjects have obstacles. which is almost the same because of the high uncertainty of these results, the suggestion from researchers is that when entering a new culture, you should study so that the uncertainty that will arise can be resolved with low uncertainty.